2018
DOI: 10.1002/hbm.24348
|View full text |Cite
|
Sign up to set email alerts
|

The neural basis of motivational influences on cognitive control

Abstract: Cognitive control mechanisms support the deliberate regulation of thought and behavior based on current goals. Recent work suggests that motivational incentives improve cognitive control and has begun to elucidate critical neural substrates. We conducted a quantitative meta-analysis of neuroimaging studies of motivated cognitive control using activation likelihood estimation (ALE) and Neurosynth to delineate the brain regions that are consistently activated across studies. The analysis included studies that in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 202 publications
(296 reference statements)
1
60
0
Order By: Relevance
“…For instance, based on a meta-analysis of neuroimaging data, Parro, Dixon, and Christoff (2017) suggested that four networks interact during cognitive-motivational exchanges (Figure 8A): a frontoparietal control network, a sensory valuation network, an interoception/salience network, and a dopaminergic midbrain-striatal network. The scheme by Parro and colleagues thus proposes that large-scale communication is important during interactions between motivation and cognition.…”
Section: Cognitive-motivational Brain Networkmentioning
confidence: 99%
See 4 more Smart Citations
“…For instance, based on a meta-analysis of neuroimaging data, Parro, Dixon, and Christoff (2017) suggested that four networks interact during cognitive-motivational exchanges (Figure 8A): a frontoparietal control network, a sensory valuation network, an interoception/salience network, and a dopaminergic midbrain-striatal network. The scheme by Parro and colleagues thus proposes that large-scale communication is important during interactions between motivation and cognition.…”
Section: Cognitive-motivational Brain Networkmentioning
confidence: 99%
“…It is also important for attentional processing more generally (Pessoa & Ungerleider, 2004). Dorsal-medial PFC is also reliably engaged during conditions involving reward manipulations (Parro, et al, 2017), as well as negative processing (Pessoa, 2013; Shackman et al, 2011). …”
Section: Cognitive-motivational Brain Networkmentioning
confidence: 99%
See 3 more Smart Citations